The Bear Grylls Adventure. Book 3, The Jungle Challenge [anglicky] - Grylls, Bear (Bear Grylls Ventures, 2019)
The third adventure in the brand-new 12-book collectible series for young readers from survival expert and Chief Scout BEAR GRYLLS. Omar is fiercely competitive and very impatient about anything that holds him back.